Anti-periodic switching dynamical system with application to chaotic system: A fixed-time fractional-order sliding mode control approach - Saim Ahmed; Hasib Khan; Ahmad Taher Azar; Jehad Alzabut (Partial Differential Equations in Applied Mathematics)
The paper presents an analysis of a new class anti-periodic switching dynamical system in chaotic power systems, incorporating a fixed-time control strategy. Theoretical insights, based on fixed point theorems (FPTs) and stability principles, are coupled with computational techniques to address system complexities. A robust control strategy utilizing fixed-time fractional-order sliding mode control is formulated to efficiently manage nonlinear dynamics. The Lyapunov proposition is employed to assess stability properties. The comparative analysis demonstrates the effectiveness of the approach in achieving trajectory tracking and fixed-time convergence goals. This interdisciplinary study bridges insights from chaotic power systems with control strategies, offering a valuable contribution to understanding and application in complex dynamical systems.